Key Insights into What Makes Public Organizations Learn from Training Programs - Reichborn-Kjennerud, Kristin (Nordic Journal of Working Life Studies, 2022)
Public organizations often operate in rigid environments with standardized procedures that are not conducive to learning, yet it is crucial that they continuously improve at solving their societal tasks in a satisfactory way. There is a lack of knowledge about what factors are important for learning to occur in public organizations. Based on a questionnaire, this study looks at how different factors condition the way in which employees perceive standardized training programs in public organizations. The study demonstrates how a training program was perceived by two different professional groups, one being more accustomed to and accepting of standardized procedures than the other. The results show that the child welfare services had a more positive attitude toward the program than did the family counseling services. Employees working in an environment that is positive to employee feedback also perceived the program as more relevant, important and useful. Employees working in an environment that prioritized competence development perceived the program to be better organized and implemented and to be relevant to their work tasks. The article argues that these factors contribute positively to organizational learning and stresses the importance for leaders to develop an environment that is positive to employee feedback.